The growth of a research field: A systematic analysis of Brazilian theses and dissertations on railways (1974–2020) - Lico, Tamires Saccharine [UNESP]; Gomes, Andreza Vellasco [UNESP]; Rocha, Nicolle Oliveira [UNESP]; Oliveira, Eduardo Romero de [UNESP] (SAGE Publications, 2022)
This paper aims to conduct a critical review of the academic works on railway history in Brazil. We read and analysed 492 theses and dissertations by graduate students in Brazil (published from 1974 to 2020). A qualitative and quantitative approach was used over time to characterise the increasing production of academic theses and dissertations on railway history in Brazil and which authors, bibliographies, archives, and historical sources have become essential for railway researchers. The results of this review indicate that several academic areas are interested in the theme and some authors have become references to the most varied railway studies. In recent decades, authors who research more specific subjects have gained greater visibility in graduation essays. The bibliography of their studies should be interpreted according to how sources change with time. Authors of the reviewed papers had to use alternatives to research railways due to archival issues and instability of access to documents.
Keywords: Brazil; Historiography; railway; theses and dissertations